Mexico’s Relationship with the Inter-American Court of Human Rights: Success or Failure? - Argente Villarreal, Arturo; Sigmond, Karen (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2019)
This article describes Mexico’s path to the protection of human rights and its relation with the Inter-American Court of Human Rights. It analyzes two major cases against the Mexican Government (Castañeda Gutman and Gonzales et al “Cotton Field”) and the contrasting results from the decisions of the Court. It questions whether being a part of this regional Court has led to the further protection of human rights by examining the aftermath of each one of the mentioned cases. It also considers other factors that must be addressed in order to see an increase in the protection of human rights in this country.